Brazilian cross-cultural adaptation of the DocCom online module: communication for teamwork - Tatiane Angélica Phelipini Borges; Marli Terezinha Oliveira Vannuchi; Suely Grosseman; Alberto Durán González (Universidade de São Paulo, 2017)
ABSTRACT Objective: to carry out the cross-cultural adaptation of DocCom online module 38, which deals with teamwork communication into Portuguese for the Brazilian contexto. Method: the transcultural translation and adaptation were accomplished through initial translations, synthesis of the translations, evaluation and synthesis by a committee of experts, analysis by translators and back translation, pre-test with nurses and undergraduate students in Nursing, and analysis of the translators to obtain the final material. Results: in evaluation and synthesis of the translated version with the original version by the expert committee, the items obtained higher than 80% agreement. Few modifications were suggested according to the analysis by pretest participants. The final version was adequate to the proposed context and its purpose. Conclusion: it is believed that by making this new teaching-learning strategy of communication skills and competencies for teamwork available, it can be used systematically in undergraduate and postgraduate courses in the health area in Brazil in order to contribute to training professionals, and also towards making advances in this field.